IMPLEMENTASI PEMBELAJARAN KITAB AT-TIBYAN FI ADABI HAMALATIL QUR’AN TENTANG ADAB MENGHAFAL AL-QUR’AN SANTRI TAHFIDZ PESANTREN KAMPUS AINUL YAQIN UNIVERSITAS ISLAM MALANG - Mitahul Ayu Fasarotin; Ahmad Subekti; Atika Zuhrotus Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Memorizing the Qur'an is an activity that can be carried out by anyone and any age. But in memorizing the Qur'an not only by memorizing, but it is also obligatory to learn the etiquette of memorizing the Qur'an from the etiquette of reading the Qur'an to how to become a memorizer of the Qur'an having the morality of mercy . This is the background of the Ainul Yaqin Islamic Boarding School Islamic University of Malang has a Tahfidzul Qur'an program complete with special book studies for students who memorize the Qur'an. Based on observations, that the etiquette of a memorizer of the Qur'an must be applied early on or from the beginning students begin to memorize. Therefore the Islamic Boarding School of Ainul Yaqin Islamic University of Malang provides the book At-Tibyan fi Adabi Hamalatil Qur'an as a book that is studied by students who are still in first grade dirosah diniyah.